Elemental Chemistry Learning Outcomes through Problem Based Learning for Tenth Grade Vocational School Students - Evi Riana Simanjuntak; Muhammad Hadeli; Meidia Farlina (Institute of Multidisciplinary Research and Community Service, 2022)
Abstract: The implementation of problem based learning to increase student’s learning outcomes is explained. This research aimed to determine the implementation of problem based learning to improve the student outcomes in senior high school (SHS) in studying chemistry. This research is conducted in SMKN 2 Palembang which the subject of research is students in tenth grade. The populations are class X TKJ 3, while the subjects were 34 students. The research is conducted by teaching students with problem based learning model followed by evaluation test in the end of each cyle to obtain learning outcomes. The results showed that the average value of Evaluation-Test for first cycle is 67,21 with the second cycle is 83,14.. The students total average of the achievement showed that the percent affectivity of problem based learning implementation showed there is significant differences between teaching by using problem based learning. So, we obtained that teaching chemistry subject by using problem based learning model is quite effective. Keywords: problem based learning, learning outcomes, elemental chemistry, classroom action research.